(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to evaluate the education of professional ethics in the accounting department and its influence on the ethical commitment of students. The influence of professional ethics education on motivation and ethical commitment of students is also done through an analysis of the influence of students’ perceptions of professional ethics education on ethical commitment of students. Research was also carried out on the organization of professional ethics education in the Accounting Department of the University of "X" in West Java even in the 2017/2018 academic year. The study was conducted using a qualitative descriptive method based on observations of institutional documents, observations of educational activities, discussions with teaching staff, and interviews with students, both using closed-ended questionnaires and open-ended questionnaires. The results of the study show that professional ethics education has been carried out effectively and has contributed to shaping the ethical commitment of students. Although it is still relatively small, professional ethics education has a significant effect in forming students’ ethical commitments, as well as professional ethics education and student motivation in a simultaneous way. In addition, this study shows that motivation mediates the influence of professional ethics education in forming students’ ethical commitments. The implication is that professional ethics education needs to be continuously developed through the development of educational processes that are not limited to professional ethics courses. Further studies need to be carried out on developing the learning process of various accounting majors to be able to include accounting education content. Thus, the process of professional ethics education can be carried out more comprehensively and with a longer duration.